Religiosity and Entrepreneurial Intention: A Study of Strawberry Generation - Soelaiman, Lydiawati; Saktiana, Galuh Mira (KINERJA, 2024)
This research will be conducted on the Strawberry Generation, better known as Generation Z, aimed at testing religiosity on entrepreneurial intentions mediated by self-efficacy, subjective norms, attitudes, and entrepreneurial motivation. This study uses a non-probability sampling technique with a purposive sampling method, with a sample size of 207 respondents. The analysis tool that will be used is SEM AMOS 22. The influence of self-efficacy, subjective norms, and entrepreneurial attitudes as a mediation of the relationship between religiosity and the intensity of entrepreneurship in Generation Z is significant, meaning that someone religious makes Generation Z have the intention to entrepreneur because it has high self-efficacy, subjective norms and also high entrepreneurial attitudes. Entrepreneurial motivation apparently does not make a religious entrepreneur intend to have an entrepreneur for Generation Z.